Pengembangan Aplikasi Terintegrasi untuk Pertukaran Informasi pada Perusahaan Manufakture Menggunakan Web Service (studi kasus pada PT.SAMI Semarang) - , Dani Sasmoko, S.T; Ir. Rudi Hartanto, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The advanced technology of computer and telecommunication has now been a significant commodity. For manufacturing industries, information from their consumers is valuable to be processed for complying the consumersâ various demands. P.T SAMI is a manufacturing industry which engages in assembly of car wires and produces products in compliance with their consumersâ demands such as: CARRIER WIRING CAM, CONNECTOR, PLUG, TERMINAL, SPACER, etc. In relation with that, the writer has made prototype software which is able to improve the companyâs performance and productivity, and bring the company and supplier to closer relations. It can also compare the time before and after applying the software with Critical Path Method (CPM). In the proposed system there is interaction between the database in the inventory and database on 4 suppliers at the time of search items, reduced working time this can be in the know at the beginning of the system takes a total of 125 minutes to do a job search and information on the new system only requires 36 minutes so that there is a lapse of time of 89 minutes. And the efficiency in work activities, this is because the data can be accessed directly in one view, and there are restrictions in the search criteria.